State regional policy as an object of scientific research. The importance of regional policy for the Russian Federation - M. A. Kartasheva (Путеводитель предпринимателя)
The author touches upon current and important topic for today’s science. The article examines regional policy from the point of view of the subject of scientific work is proved by its novelty and significance. Detailed analysis: public policy, regional policy, proved their relevance to modern science and research. This work defines the importance of a true regional policy for the management of the state. The author makes an overview of the problems of regional development in Russia, their preconditions and consequences. Examples of positive experience of implementation of cluster policy.